Clinical psychologists' perceptions of the phenomenon of schizophrenia in a psychiatric setting in the Eastern Cape, South Africa - Hamman, Colette (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
Numerous international and South African scholars are critical of the dominant research on the phenomenon of schizophrenia. Rather than refuting dominant biomedical psychiatric conceptualisations of schizophrenia, there is a call for incorporating a focus on the psychology of the person diagnosed with schizophrenia. In South Africa, the integration of the psychosocial components of psychotic experiences into the understanding and treatment of psychosis are still neglected in biomedically-focused psychiatric settings. In relation to this call, the role of clinical psychologists working within these settings seems pertinent. Against this background, this study aimed to explore and describe the perceptions of clinical psychologists, working in a psychiatric setting in South Africa, in relation to the phenomenon of schizophrenia. Informed by a social constructionist theoretical framework, this study utilised a qualitative research design and a semi-structured interview schedule. In-depth, individual interviews were conducted with three clinical psychologists and the transcribed interviews were analysed using thematic analysis. From the data, perceptions were identified as largely polarised in relation to the phenomenon of schizophrenia. These polarised perceptions included: Physical impact of schizophrenia versus social impact of schizophrenia; rehabilitation of schizophrenia versus recovery within schizophrenia; diagnostic frameworks as useful versus diagnostic frameworks as limiting; and institutionally-defined identity versus self-defined identity. In terms of these polarised perceptions, an overarching theme of the medicalisation versus the demedicalisation of schizophrenia was identified. Therefore, the perceptions of clinical psychologists in this study were largely polarised towards either a medicalisation of the phenomenon of schizophrenia or a demedicalisation of it. However, perceptions were also identified that evidenced an integration of the two sides of the polarities, and a holding of tension between seemingly incompatible or incongruent frameworks. The participants perceived psychologists as positioned in the middle ground between the medicalisation and demedicalisation of schizophrenia in a biomedical psychiatric setting. In response to the call for a focus on the psychology of the person diagnosed with schizophrenia, the findings support both the value and the need for an "integration of polarised perceptions" , "holding of the tension" , and "middle ground positioning" of clinicians between medicalised and demedicalised aspects of the phenomenon of schizophrenia.
Keywords: Schizophrenia -- Diagnosis -- South Africa; Schizophrenia -- Treatment -- South Africa; Schizophrenics -- Rehabilitation -- South Africa; Schizophrenics -- South Africa -- Case studies